Creative Genius as Causal Agent in History: William James's 1880 Theory Revisited and Revitalized. Issue 4 (December 2018) - Simonton, Dean Keith
Near the onset of his illustrious career, the psychologist William James proposed a theory of how individual genius can exert a unique and enduring causal impact on the history of civilization. After first attacking the prevailing view that sociocultural determinism rendered individual creators and leaders mere epiphenomena, James argued that the causal effect of the genius paralleled that of the spontaneous variation or mutation in the theory of evolution by natural selection. Although his specific arguments suffer severe problems even from the standpoint of his own theory, current psychological research on creativity and genius indicate how his basic thesis can be revised and updated with respect to creative genius. This revision and updating concentrates specifically on what is known about the behavioral productivity, thinking processes and procedures, personality characteristics, and early developmental experiences in highly creative individuals. These modern enhancements then lead to the integrated discussion of Jamesian free will and the causal agency of the creative genius. The net result is a revitalized theory of how it even becomes possible for single individuals to make creative choices that not only may cause changes in their own lives, but also alter the course of world history.